Examining the Effects of Temperature on Recombination in Wheat - Coulton, Alexander; Burridge, Amanda J.; Edwards, Keith J. (Frontiers in Plant Science, 2020)
Meiotic recombination plays a crucial role in the generation of new varieties. The effectiveness of recombination is limited by the distribution of crossover events, which in wheat and many other crops is skewed toward the distal regions of the chromosomes. Whole-genome sequencing of wheat has revealed that there are numerous important genes in the pericentromeric regions, which are inaccessible to manipulation due to the lack of crossover events. Studies in barley have shown that the distribution of recombination events can be shifted toward the centromeres by increasing temperature during meiosis. Here we present an analysis of the effects of temperature on the distribution and frequency of recombination events in wheat. Our data show that although increased temperature during meiosis does cause an inward shift in recombination distribution for some chromosomes, its overall utility is limited, with many genes remaining highly linked.